The Impact of Health Information Systems on Improving the Quality of Medical Services in Community Health Centers (Literature Review) - alfi syahrina hidayat; putri lestari; nadhila hasibuan; salsabila nazuha; yasmin novithaharah suprianto; sri hajijah purba (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Health Information Systems (HIS) are a crucial element in improving the efficiency and accuracy of medical services in community health centers. This study aims to analyze the impact of HIS implementation on the quality of healthcare services, using a Systematic Literature Review (SLR) approach. The analysis process involved identifying 300 relevant articles through academic databases, such as Taylor and Francis and Scopus, which were then selected into 10 primary articles based on inclusion criteria. This study explored the impact of HIS on service efficiency, data accuracy, and evidence-based decision-making. The analysis results indicate that the implementation of HIS, such as the Community Health Center Management Information System (SIMPUS) and web-based applications, significantly contributes to accelerating services, reducing patient waiting times, and increasing user satisfaction. However, challenges such as limited human resources, inadequate technological infrastructure, and the complexity of data management remain major obstacles. System integration, such as bridging systems, and the development of web-based applications have proven effective in addressing some of these obstacles. This study concludes that HIS has a positive impact on improving the quality of healthcare services in community health centers, although its implementation requires better infrastructure support and human resource training. Technological integration and innovation efforts are key to optimizing the benefits of HIS in supporting efficient, patient-centered healthcare services.